GROUP COMMUNICATION INCREASES STUDENTS' LEARNING MOTIVATION ONLINE - Muslim Muslim (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
This study attempts to determine the impact of group communication generated at IPB Bogor on IPB students' learning motivation. Group communication was the independent variable in this study, whereas learning motivation was the dependent variable. Indicators of social connection function, educational function, persuasive function, problem solving and decision-making function, and therapeutic function are used to measure group communication variables. Intrinsic elements, such as interests, ambitions, and individual circumstances, are measured, as are extrinsic influences, such as worry about punishment, rewards, and praise, the involvement of parents, teacher wars, and environmental conditions. From April to May 2021, the research was conducted at Bogor Agricultural Institute for Bachelor and Vocational Programs. As it studies influences, the research method employed in this study is a quantitative approach utilizing explanatory questionnaires. The study's sample consisted of 100 persons chosen at random from a total of 22,744 people who met the sample criteria. Non Probability Sampling, often known as Accidental Sampling, is the sampling approach employed. Data analysis in the form of simple regression analysis is used in this study. The results of the questionnaires for each indication of group communication and enthusiasm to learn are summarized in 30 statements. According to the findings of this study, group communication has a significant impact on student learning motivation.